Epidemiology of sudden infant death syndrome in Mexico, 2005–2020 - Martínez-Valdez, Libny; Richardson, Vesta; Bautista-Márquez, Aurora; Hernández-Ávila, Mauricio (Frontiers in Pediatrics, 2022)
Background. Sudden Infant Death Syndrome (SIDS) constitutes one of the main causes of mortality in children under one year of age in developed countries; it´s frequency to varies geographically. In Mexico the real incidence of SIDS is not known. Methods. National databases of deaths in children under one year of age, from 2005 to 2020, were analyzed, due to Sudden Unexpected Infant Death (SUID) [SIDS (R95), accidental suffocation in a sleeping environment (W75), and other ill-defined and unspecified causes of mortality (R99), according to the International Classification of Diseases, tenth revision (ICD 10)]. Mortality rates per year of occurrence due to SUID and their subcategories were calculated. Simple frequencies of SIDS were obtained per year and month of occurrence, state of residence, age, place of death, and access to social security services. Results. In the study period 473 545 infant deaths occurred; 7 714 (1.62%) deaths were due to SUID; of these, 6 489 (84%) were due to SIDS, which is among the 10 leading causes of infant death in Mexico. The average mortality rate for SUID was 22.4/100 000 live births, for SIDS was 18.8/100 000 live births. Mortality rates within the states were variable, ranging from 2.4/100 000 to 105.1/100 000 live births. In 81% of SIDS records there was no autopsy; 38% of deaths due to SIDS occurred in infants under one month of age, up to 87% of deaths occurred in families without social security services or it was unknown, and 76.2% of deaths occurred at home. Deaths were more frequent during the last months of autumn and during winter. Conclusion. In Mexico there is an underregistry of SIDS as cause of death, along with other SUID categories. Health workers need to be trained to improve diagnosis and data registration, including the practice of autopsies; additionally, it is necessary to implement a public health campaign.